2010
DOI: 10.1111/j.1744-7348.2010.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Citrus dwarfing viroid: effects on tree size and scion performance specific to Poncirus trifoliata rootstock for high-density planting

Abstract: The term 'transmissible small nuclear ribonucleic acids' (TsnRNAs) describes well-characterised viroid RNA species that do not induce any pronounced disease syndromes in specific citrus hosts, but rather act as regulatory genetic elements modifying tree performance. The canopy volume (CV) of 13-yearold navel orange trees (Citrus sinensis) on Poncirus trifoliata rootstock treated with TsnRNA-IIIb (syn. Citrus dwarfing viroid) was reduced by 45% and 53.5% in standard-density (6 m × 6.7 m) or high-density (3 m × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Described almost 100 years ago, cross-protection has been applied to promote the health of crops, including cucurbits, papaya and citrus (Ziebell and Carr, 2010). Commercial use of viroids is approved in United States to induce desired dwarfing in citrus trees and increase yields per land surface unit (Vidalakis et al, 2011). Plant viruses have been used as herbicides to control invasive weeds by inducing lethal hypersensitive reactions (Harding and Raizada, 2015).…”
Section: Cutting-edge Applications Of Plant Virusesmentioning
confidence: 99%
“…Described almost 100 years ago, cross-protection has been applied to promote the health of crops, including cucurbits, papaya and citrus (Ziebell and Carr, 2010). Commercial use of viroids is approved in United States to induce desired dwarfing in citrus trees and increase yields per land surface unit (Vidalakis et al, 2011). Plant viruses have been used as herbicides to control invasive weeds by inducing lethal hypersensitive reactions (Harding and Raizada, 2015).…”
Section: Cutting-edge Applications Of Plant Virusesmentioning
confidence: 99%
“…Careful monitoring may help to avoid such transmissions in the future. Locally restricted viroid infections, such as dwarfing of citrus trees for easier harvesting and less water consumption ( 187 , 188 ), will require exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, studies conducted prior to the HLB era in Florida have shown that grapefruit trees bear more fruit even when subjected to rigid tree size control at high-density planting [43]. Previous studies have also demonstrated that high-density plantings result in greater production per area [53,54] especially under HLB-endemic conditions [9,16]. New groves planted at higher densities in Florida can be more profitable than groves planted at low densities [7,14].…”
Section: Number Of Fruit Fruit Size and Fruit Yieldmentioning
confidence: 99%